Biofilm development on carbon nanotube/polymer nanocomposites. Issue 3 (12th May 2016) - Goodwin, David G.; Xia, Z.; Gordon, T. B.; Gao, C.; Bouwer, E. J.; Fairbrother, D. H.
Abstract : Carbon nanotube/polymer nanocomposite surfaces impact biofilm development through the cytotoxic effect of exposed carbon nanotubes on microorganisms. Abstract : Biofilms have the potential to form on polymer nanocomposites containing carbon nanotubes (CNT/PNCs) when they come into contact with microorganisms in aqueous environments post-consumer use. In this study we explored the effect that CNT/PNC surface characteristics have on biofilm development, as compared to the unmodified polymer, under drip flow and static conditions. Specifically, we examined biofilm formation on CNT/PNCs where CNTs are initially present below the PNC surface but accumulate as a result of polymer biodegradation and where CNTs are initially present at the PNC surface. CNT/PNCs composed of oxidized multi-wall CNTs and poly- ε -caprolactone (PCL), a biodegradable polymer, were prepared and exposed to Pseudomonas aeruginosa ; biofilm development was monitored using LIVE/DEAD staining. As prepared, CNTs were absent at the CNT/PCL surface, giving rise to an initially benign CNT/PCL-microbial interaction, analogous to that observed on PCL. As biofilm development progressed, however, PCL biodegradation caused CNTs to accumulate at the surface leading to an antimicrobial effect and eventually a full (2% w/w CNT) or partial dead (0.5% w/w CNT) layer of microorganisms. At later stages, active biofilm formation occurred on top of a protective layer of dead microorganisms indicating that biofilm growth on CNT/PCL nanocomposites was delayed, but not inhibited. CNTs also accumulated at CNT/PCL surfaces as a result of a simulated weathering process and these surfaces exhibited immediate cytotoxicity. However, "live-on-dead" biofilm formation was still ultimately observed. Qualitatively similar trends of biofilm development were observed under drip flow and static conditions although the structure and rates of biofilm formation differed.